(untitled) (2025)
The purpose of this study is to improve students’ psychomotor skills through education with ball relay games on the 100-meter running material in class XI.4 of SMA Negeri 11 Semarang. This research is a classroom action research conducted in two cycles. This research was conducted in semester 2, academic year 2024/2025 in March to May with a total of 36 students. Data collection techniques through observation, interviews and practical tests. Data analysis techniques in the form of descriptive analysis through observation of students in participating in 100-meter running learning on the psychomotor aspect. The results of this study indicate that students’ psychomotor scores in the pre-cycle had a completion rate of 57.7% with an average score of 60.69. In cycle I, the completion rate was 72.2% with an average score of 73,33. In cycle II, there was an increase in completion rate of 80.5% with an average score of 79,33. In this study, the results showed that using the ball relay game approach can improve psychomotor skills for students.